THE LINK BETWEEN THE LISBON STRATEGY AND THE COHESION POLICY OF THE EUROPEEAN UNION - Lavinia Florentina CHIRILĂ, (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2010)
Union, the Lisbon Strategy “has proved its worth”. Since its relaunch in 2005, more than 6.5 million jobs have been created in Europe and unemployment has fallen to the lowest level recorded in the last 25 years. All these great achievements have been purchased through the four priority areas sustained by the Lysbon Strategy, which are investing in people and modernising labour markets; energy and climate change; strengthening economic competitiveness; promoting knowledge and innovation. But which is the link between the Lisbon strategy and the regional policy as the KOK report emphasized? Which are the perspectives after 2013? are some of the question that the present paper examines, taking into account the results that have been registered in Romania and its regions so far.